Alterações morfológicas, fisiológicas e bioquímicas em Cordia trichotoma (vell.) arrab. ex steud em resposta a adubação mineral e orgânica no plantio - Berghetti, Álvaro Luís Pasquetti (2017)
Cordia trichotoma species (louro-pardo) is widely distributed in tropical and subtropical forests at South America. Its wood has high economic value and it is considered one of the priority tree species for planting destined to reestablishment altered area and for commercial purposes. However, researches related to morphological, physiological and biochemistry performance are incipient, mainly associated to the use of water-retaining polymers as well as the fertilization for suitable growing in the field. In this sense, the present study was shared in two chapters: Chapter I aimed to verify the behavior of C. trichotoma seedling submitted over four phosphor applications (0, 120, 240 e 360 Kg of P2O5 ha-1), with presence and absence of water-retaining polymers (5 g L-1 per seedling-1). In the Chapter II was studied the influence of different types of fertilizers (cattle manure, poultry manure and mineral fertilizer) in the C. trichotoma, with and without the presence of water-retaining polymers. The planting was conducted on a Sandy Typic Hapludalf, at Central region of Rio Grande do Sul State, Brazil. For seedlings evaluation, was measured morphological (height and stem diameter, leaf area and dry matter of shoot and root), physiological (chlorophyll a fluorescence), biochemistry parameters (photosynthetic pigments and phosphatase acid enzyme activity) and nutrients content in the leaf. In general, it was evident the occurrence of high rainfall index after planting phase and, there was no influence of the use of water-retaining polymers in the survival and seedlings growth. In the Chapter I, was noticed that C. trichotoma species require soil fertility, demanding phosphatase fertilization. It is recommended the use of near 220 Kg P2O5 ha-1 for seedling achieve high growth in the shoot, stem diameter and dry matter of shoot and root. This fertilizer content is recommended for more exploitation of luminous energy and less loss of fluorescence energy. In the Chapter II, was showed for this species that fertilization with cattle manure can be considered alternative option, replacing mineral fertilization originated from scare sources and with high purchase cost. The use of 10 liters of cattle manure per seedling provide suitable growth and photosynthetic activity. In the present study, we noticed that the evaluation of emission fluoresce of chlorophyll a and phosphatase acid enzyme activity can be used to identified alteration in plants metabolism caused by low nutrients availability as well as to control the demand of seedling fertilization of this species.